Application of the new structural solutions in the seeders for precision sowing as a resource saving direction - Boiko, Anatolii; Popyk, Pavlo; Gerasymchuk, Iurii; Bannyi, Oleksandr; Gerasymchuk, Nataliia (Eastern-European Journal of Enterprise Technologies, 2018)
The study reported here provides a possibility to improve the reliability of conducting a technological process of dispensing the seeds, which affects the efficiency, that is, the cost of seed material, by introducing a dispenser of targeted action to the design of the sowing unit. The pneumomechanical machine with the dispenser of targeted action has been developed to conduct our research. The suction active cells of the dispenser change their position at rotation in order to better target the dispensed seed. Experimental research has confirmed that the dispenser with targeted action improves dispensing conditions for sowing seeds by using the active suction cells. The result of using the new structural solution for the dispenser is a 12 % increase in the precision of implementing the technological process of forming a regular one-grain flow of seeds. We have devised a procedure for experimental research into establishing and determining the reliability parameters when the unit performs a technological process of sowing. We have established patterns in the emergence of gaps and double items depending on the basic technological parameters in the operation of a sowing device: motion speed of the dispensing element and degree of rarefaction in the vacuum chamber. The research revealed that soybean seeds almost do not form double items with the probability of their occurrence close to zero. We have determined values for the stochastic indicators of precision in the implementation of technological process of sowing, which confirmed the advantages of the unit with targeted action as compared to a standard one. To assess the performance of sowing units’ operation, it is expedient to use a comprehensive indicator for the probability of sowing precision, which includes the likelihood of gaps, the probability of the formation of double items, and the likelihood of seed deviations from the specified point of seeding under an almost missing inversion. The probability of sowing precision for the experimental unit, as a comprehensive indicator for the improved efficiency of its application, is larger than that of the standard one by 0.11. The result of using the new structural solution for the dispenser is the improved precision of execution of technological process of forming a regular one-grain flow.